Perioperative active warming versus no active warming during caesarean section for preventing neonatal hypothermia in women performing skin-to-skin contact: a randomized controlled trial. - Vilinsky-Redmond, Aliona (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2020)
This dissertation reviews the current literature and disseminates the methods/findings of a Randomised Controlled Trial about the prevention of neonatal hypothermia in women performing skin-to-skin contact during their elective caesarean section. It explores the effects of neonatal hypothermia on the newborn’s wellbeing and the prevalence of neonatal hypothermia after caesarean section, while at birth skin-to-skin contact is performed. Collectively,this study articulates the current knowledge about the unclear impact of maternal perioperative hypothermia on the frequency of neonatal hypothermia during and after caesarean section while investigating a method of maternal active management in order to reduce the frequency of both perioperative neonatal and maternal hypothermia, while at birth skin-to-skin contact is performed. The management of neonatal and maternal hypothermia after caesarean section, while at birth skin-to-skin contact is performed, is a problem not adequately addressed in current literature. As a result there is no clear method of prevention of its occurrence. Prevention would reduce not only the health implications that hypothermia has on the wellbeing of both newborns and their mothers, but also would reduce/minimize the newborn-maternal separation in order to manage hypothermia. This would increase the duration of skin-to-skin contact/breastfeeding and the associated health benefits to both mothers and newborns. Since the existing knowledge on skin-to-skin contact is based on studies conducted after vaginal birth, there is a dearth of knowledge on the applicability of this knowledge on the population of women undergoing caesarean section. Moreover, the increasing global rates of caesarean section and the lack of standardization of skin-to-skin contact during caesarean section, indicate that more women and newborns will be deprived of the health benefits of skin-to-skin contact. In order to overcome this burden, a Randomized Controlled Trial was performed to provide evidence on the hypothesis that perioperative maternal active warming (administration of warm IV fluids) would reduce the frequency of maternal and neonatal hypothermia during caesarean section. By reducing the frequency of maternal and neonatal hypothermia the impact that that had on maternal/newborn separation was reviewed. The prevention of maternal and neonatal hypothermia during caesarean section thus reveals a deep gap in the current knowledge and clinical practice of the maternity operating theatres by showing that it is often not accommodated, or promoted in this settings because there was insufficient evidence about the safety and applicability of perioperative active warming on this specific population. Yet, prevention of perioperative hypothermia with the use of active warming methods, is a widely established practice for the general population undergoing general major operations. As long as a maternal active warming is safe and effective during caesarean section then the frequency of maternal/newborn hypothermia and their separation can be significantly be reduced
APPROVED
Keywords: Elective caesarean section; Neonatal hypothermia; Skin-to-skin contact; Perioperative active warming